1986
DOI: 10.1111/j.1095-8649.1986.tb05184.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intra‐ and inter‐specific competition on the survival and growth of stocked juvenile Atlantic salmon, Salmo solar L., and resident trout, Salmo trutta L., in an upland stream

Abstract: The relative effects of inter-and intra-specific competition on the survival and growth of stocked salmon were investigated in an upland trout stream during summer and winter sampling periods. The stream was divided into two areas by an impassable fish barrier, and trout were removed from the upstream section prior to 2 years of salmon stocking. Salmon fry stocked into the cleared area survived more than twice as well and grew significantly larger than those stocked into the area containing trout and older sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 9 publications
3
61
0
Order By: Relevance
“…For example, the increased cover and bank shelter provided by large riparian trees and their roots create habitats that are strongly preferred by brown trout but not necessarily by juvenile salmon (Armstrong et al 2003). Several studies have shown potential negative effects of resident trout on Atlantic salmon via competition (Kennedy & Strange 1986, Hearn 1987) and predation (Henderson & Letcher 2003), but others have found little evidence of a negative interaction, and all of these studies have major constraints with respect to extension of their results to population impacts. In addition, mature riparian forests may provide denning and perching habitats for mammalian and avian predators (DeGraaf & Yamasaki 2000; some of which may themselves be conservation targets) but this topic has not been well studied in Atlantic salmon rivers.…”
Section: Complex Interactionsmentioning
confidence: 99%
“…For example, the increased cover and bank shelter provided by large riparian trees and their roots create habitats that are strongly preferred by brown trout but not necessarily by juvenile salmon (Armstrong et al 2003). Several studies have shown potential negative effects of resident trout on Atlantic salmon via competition (Kennedy & Strange 1986, Hearn 1987) and predation (Henderson & Letcher 2003), but others have found little evidence of a negative interaction, and all of these studies have major constraints with respect to extension of their results to population impacts. In addition, mature riparian forests may provide denning and perching habitats for mammalian and avian predators (DeGraaf & Yamasaki 2000; some of which may themselves be conservation targets) but this topic has not been well studied in Atlantic salmon rivers.…”
Section: Complex Interactionsmentioning
confidence: 99%
“…In the streams selected by us, there were no fish predators. The absence of predators in the streams has a significant impact on the survival and growth of juvenile salmonids (Kennedy and Strange 1986) Analysis of the stomach contents of grayling fry show that the majority of all the taxa of the macroinvertebrates that were found in the stomachs of the fish occurred more numerously in the LFG than in the PFG fish. The same results were observed in the studies of Czerniawski et al (2014), where the LFG hatchery-reared trout, fed the same food as the grayling in the present study, had in their stomachs more organisms that the PFG fish.…”
Section: Discussionmentioning
confidence: 99%
“…Fish of the same species might be expected to compete more than fish of different species due to the commonality in their ecological requirements at similar life stages Kennedy and Strange 1986).…”
Section: Drift Samples (%)mentioning
confidence: 99%
“…Hatchery-reared salmonids may compete with wild fish (Bachman 1984;Vincent 1987). Releases of large numbers of hatchery-reared fish increase the total density of fish in certain areas for varying lengths of time and competition for limited resources increases when fish density increases Kennedy and Strange 1986;Heggenes 1988;Christiansen et al 1992). Social interactions between hatchery and wild fish may negatively impact the wild fishes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation